1982
DOI: 10.1113/jphysiol.1982.sp014299
|View full text |Cite
|
Sign up to set email alerts
|

Fusimotor reflexes in triceps surae elicited by natural stimulation of muscle afferents from the cat ipsilateral hind limb

Abstract: SUMMARY1. Experiments were performed in forty-one cats anaesthetized with chloralose. 2. The aim of the study was to investigate whether activity in stretch-sensitive muscle receptors may cause reflex effects in fusimotor neurones.3. Activity in fusimotor neurones was studied indirectly by recording from primary and secondary muscle spindle afferents ofthe triceps surae muscle. The mean rate of firing of the afferents as well as either dynamic index (during ramp extension) or modulation (during sinusoidal exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…However, recent findings ofconsiderable differences between a-and y-motoneurones with regard to reflexes from muscle, skin and joint inputs (Appelberg et al , 1982(Appelberg et al , 1983a make it less likely that a parallelism in a-and y-activity is a general rule. Therefore, if the recurrent inhibitory system acts as a gain regulator, it seems likely that the recurrent control ofy-motoneurones should, at least in part, be specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent findings ofconsiderable differences between a-and y-motoneurones with regard to reflexes from muscle, skin and joint inputs (Appelberg et al , 1982(Appelberg et al , 1983a make it less likely that a parallelism in a-and y-activity is a general rule. Therefore, if the recurrent inhibitory system acts as a gain regulator, it seems likely that the recurrent control ofy-motoneurones should, at least in part, be specific.…”
Section: Discussionmentioning
confidence: 99%
“…Thus there seem to be differences between the recurrent control of z-and y-motoneurones, which add to the arguments against the concept of stereotyped a-y linkage (see Appelberg, Hulliger, Johansson & Sojka, 1981, 1982, 1983Johansson, 1981 (Wilson, 1959;Wilson, Diecke & Talbot, 1960;Wilson & Burgess, 1962a, b) is caused by Renshaw cells feeding inhibition to group Ia inhibitory interneurones, resulting in disinhibition of a-cells (Hultborn et al 1971). Since group Ia inhibitory effects seem to be rare or absent in y-motoneurones (Appelberg et al 1983a), the findings of recurrent facilitatory actions must be interpreted in another way.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a prevalence of excitation from group II muscle afferents in dynamic y-motoneurones is also supported by other experimental evidence. Following our initial preliminary account on this aspect of y-cell reflex organization (Appelberg et al 1977), Noth & Thilmann (1980) and Noth (1981) (Appelberg, Hulliger, Johansson & Sojka, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Using natural stimulation of muscle receptor afferents Appelberg, Hulliger, Johansson & Sojka (1979, 1982b have shown that the fusimotor reflexes which so far have only been demonstrated by electrical stimulation, can also operate under more natural conditions. Particularly relevant in the present context is the finding that the reflex activation of triceps fusimotor neurones was sufficiently powerful to drastically alter the responses of triceps primary afferent units to stretching of the parent muscle.…”
Section: B Appelberg and Othersmentioning
confidence: 99%